Photoperiod and temperature constraints on the relationship between the photochemical reflectance index and the light use efficiency of photosynthesis in Pinus strobus - Fréchette, Emmanuelle (Tree Physiol, 2016)
The photochemical reflectance index (PRI) is a proxy for the activity of the photoprotective xanthophyll cycle and photosynthetic light use efficiency (LUE) in plants. Evergreen conifers downregulate photosynthesis in autumn in response to low temperature and shorter photoperiod, and the dynamic xanthophyll cycle-mediated non-photochemical quenching (NPQ) is replaced by sustained NPQ. We hypothesized that this shift in xanthophyll cycle-dependent energy partitioning during the autumn is the cause for variations in the PRI–LUE relationship. In order to test our hypothesis, we characterized energy partitioning and pigment composition during a simulated summer–autumn transition in a conifer and assessed the effects of temperature and photoperiod on the PRI–LUE relationship. We measured gas exchange, chlorophyll fluorescence and leaf reflectance during the photosynthetic downregulation in Pinus strobus L. seedlings exposed to low temperature/short photoperiod or elevated temperature/short photoperiod conditions. Shifts in energy partitioning during simulated autumn were observed when the pools of chlorophylls decreased and pools of photoprotective carotenoids increased. On a seasonal timescale, PRI was controlled by carotenoid pool sizes rather than xanthophyll cycle dynamics. Photochemical reflectance index variation under cold autumn conditions mainly reflected long-term pigment pool adjustments associated with sustained NPQ, which impaired the PRI–LUE relationship. Exposure to warm autumn conditions prevented the induction of sustained NPQ but still impaired the PRI–LUE relationship. We therefore conclude that alternative zeaxanthin-independent NPQ mechanisms, which remain undetected by the PRI, are present under both cold and warm autumn conditions, contributing to the discrepancy in the PRI–LUE relationship during autumn.